Influencing factors of decision-making for emerging technologies adoption in the construction industry - Fakhira Fathini, Mohd Khudzari (2023)
The contemporary era is marked by an unprecedented pace of technological evolution, compelling industries globally to adapt or risk obsolescence. Particularly in regions like Malaysia, with a dynamic economic landscape and ambitious infrastructural aspirations, the urgency to stay abreast with technology becomes even more palpable. Amidst the accelerating digital transformation across various industries, the Malaysian construction sector confronts the imperative to adopt emerging technologies. This study aspires and aims to methodically identify the key factors influencing emerging technologies (ETC) adoption and to develop a comprehensive structural equation model to analyze their relationships, providing a deeper understanding of the ETC dynamics within architectural, engineering, and construction (AEC) arenas. Driven by these aims, the triad of objectives are identified influential factors and scrutinize its most influential factors to adopt ETC in Malaysian Construction Industry and establish the relationship between the most influential factors to adopt emerging technologies in the Malaysian Construction Industry by modelling the underlying construct. Embracing a mixed-method approach, the initial qualitative phase involved semi-structured interviews with project managers from G7-rated Malaysian construction entities. The insights from these interactions, combined with a systematic literature review of 211 articles, laid the groundwork for the subsequent quantitative phase, which entailed disseminating questionnaires to a broader spectrum of construction professionals. The questionnaire survey distilled 35 influencing factors from both the literature and the practitioner dialogues. Through rigorous data analysis techniques including Average Score Ranking, Agreement Analysis, Exploratory Factor Analysis (EFA), and Structural Equation Modelling (SEM), these factors gravitated around three primary themes: organizational resources, goals, and strategies, with the strategies presenting as a decisive influencing factor in ETC adoption decisions. Conclusively, this exploration amplifies our grasp of the influencing factors that either bolster or inhibit ETC adoption, offering invaluable insights to both academia and industry to optimize the integration of emerging technologies within the construction landscape.